(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Distribution of antimony in the phases of the Sb-Fe-O-SiO2-CaO system has been determined for the first time through high-temperature experiment and quenching techniques, followed by Electron probe X-ray microanalysis (EPMA) in air (Ptot = 1 atm, PO2 = 0.21 atm) under SiO2 saturation. In this study, the phases were quantified in the temperature range of 900 °C 1200 °C and the effect of Fe/SiO2 (mass fraction) and CaO/SiO2 (mass fraction) on the Sb2O3 content in the Sb-Fe-O-SiO2-CaO system were investigated at 1200 °C. The results indicated that the Sb-containing phase mainly existed in the solid solution phase at 1200 °C. The Sb2O3 content in the solid solution phase increased dramatically as the temperature increased, from 7.52 wt% at 1100 °C to 17.36 wt% at 1200 °C. Lowering the values of CaO/SiO2 and Fe/SiO2 in the smelting process can effectively reduce the Sb2O3 content in the slag. The verification experiment results implied that the antimony content in slag is 0.57 wt%, the crude antimony rate is lower than 4% and the crude antimony grade is beyond 94 wt%, which can realize the reduction of antimony content in slag.